2020
DOI: 10.3389/fmicb.2020.560179
|View full text |Cite
|
Sign up to set email alerts
|

Broad Virus Detection and Variant Discovery in Fecal Samples of Hematopoietic Transplant Recipients Using Targeted Sequence Capture Metagenomics

Abstract: Pediatric allogeneic hematopoietic stem cell transplantation (HSCT) patients often suffer from gastro-intestinal (GI) disease caused by viruses, Graft-versus-Host Disease (GVHD) or a combination of the two. Currently, the GI eukaryotic virome of HSCT recipients remains relatively understudied, which complicates the understanding of its role in GVHD pathogenicity. As decisions regarding immunosuppressive therapy in the treatment of virus infection or GVHD, respectively, can be completely contradicting, it is cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Therefore, an early panel, Virocap, used 337 viral species genomes as a reference for bait design [ 113 ]. The Virocap panel comprised approximately 2 million baits and was applied to a study detecting gastrointestinal (GI) viruses in transplant recipients for hematopoietic stem cells, specifically to differentiate between graft-versus-host disease or GI disease caused by viral pathogens [ 114 ]. Common culprits such as norovirus (see also [ 115 ]) and adenovirus positive in PCR diagnostics were also positive using HC, but a diversity of clinically relevant viruses, especially in those without any positive PCR result for common GI disease viral pathogens, were also captured, once again highlighting the need for judicious interpretation of results is required when using CM as a possible avenue for diagnosis.…”
Section: Hybrid-capture Target Enrichment For Pathogensmentioning
confidence: 99%
“…Therefore, an early panel, Virocap, used 337 viral species genomes as a reference for bait design [ 113 ]. The Virocap panel comprised approximately 2 million baits and was applied to a study detecting gastrointestinal (GI) viruses in transplant recipients for hematopoietic stem cells, specifically to differentiate between graft-versus-host disease or GI disease caused by viral pathogens [ 114 ]. Common culprits such as norovirus (see also [ 115 ]) and adenovirus positive in PCR diagnostics were also positive using HC, but a diversity of clinically relevant viruses, especially in those without any positive PCR result for common GI disease viral pathogens, were also captured, once again highlighting the need for judicious interpretation of results is required when using CM as a possible avenue for diagnosis.…”
Section: Hybrid-capture Target Enrichment For Pathogensmentioning
confidence: 99%
“…Moreover, decreased detection rates were noted for bacteriophages, except for Siphoviridae. A similar work was carried out by a Dutch group [13]. The authors used the original ViroCap system to study fecal samples, with a large panel of probes for 34 families of DNA and RNA viruses (a total of 337 species).…”
Section: Gut Human Virome After Hsctmentioning
confidence: 99%
“…Moreover, these earlier data showed that this hybridisation panel of approximately two million capture probes designed in 2015 was suited for the detection of novel coronaviruses by reactivity with other vertebrate betacoronavirus probes 10 . During the past years, this specific hybridisation panel distributed by Roche has been adopted in a broad range of different clinical 15,[22][23][24][25][26][27][28][29] and zoonotic settings 22,29,30 is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review)…”
Section: Introductionmentioning
confidence: 99%